2018
DOI: 10.1038/mi.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

CD103+CD11b+ mucosal classical dendritic cells initiate long-term switched antibody responses to flagellin

Abstract: Antibody responses induced at mucosal and nonmucosal sites demonstrate a significant level of autonomy. Here, we demonstrate a key role for mucosal interferon regulatory factor-4 (IRF4)-dependent CD103 þ CD11b þ (DP), classical dendritic cells (cDCs) in the induction of T-dependent immunoglobulin G (IgG) and immunoglobulin A (IgA) responses in the mesenteric lymph node (MLN) following systemic immunization with soluble flagellin (sFliC). In contrast, IRF8-dependent CD103 þ CD11b À (SP) are not required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
(77 reference statements)
0
26
0
Order By: Relevance
“…Intraperitoneal immunization of sFliC induces a rapid MyD88-dependent accumulation of intestinal-derived CD103 + cDC2 in the MLN ( 1 , 3 ). To analyse the role of TLR5 in this response, WT and TLR5 −/− mice were immunized with sFliC and the cDC response analyzed by flow cytometry and in situ by immunofluorescence 24 h post-immunization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intraperitoneal immunization of sFliC induces a rapid MyD88-dependent accumulation of intestinal-derived CD103 + cDC2 in the MLN ( 1 , 3 ). To analyse the role of TLR5 in this response, WT and TLR5 −/− mice were immunized with sFliC and the cDC response analyzed by flow cytometry and in situ by immunofluorescence 24 h post-immunization.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that sFliC can drive a long-term mucosal adaptive response after i.p. immunization ( 1 , 3 ). Furthermore, we also have shown that s.c. and i.p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showing that the migration and upregulation of costimulatory molecules by DCs in response to TLR stimuli in vivo can result from trans-activation of DCs therefore suggest that differences in migration capacities may not be linked to the polarization of T cell responses. However it is important to note that not all TLR ligands can induce migration in trans, as signaling through TLR5, that is only expressed on cDC2, does not induce cDC1 migration in vivo (Flores-Langarica et al, 2017). Taken together, these findings indicate that TLR based adjuvants and targeting need to be examined individually for their impact on specific DC subsets if their effects on the immune system are to be understood in depth.…”
Section: Subsets Differ In Type I Ifn Signaling Requirements For Mmentioning
confidence: 99%